ANALISIS HAMBATAN KUALITAS SISTEM INFORMASI AKUNTANSI PERBANKAN DI ERA INDUSTRI 4.0 - Rapina Rapina Rapina; Hanny Hanny; Nunuy Nur Afiah (Sekolah Tinggi Ilmu Ekonomi Indonesia (STIESIA) Surabaya(STIESIA) Surabaya, 2021)
The fourth Industrial Revolution significantly changed banking products and services. The bank needs relevant and quality accounting information to support them in providing products and services to customers. The required accounting information is generated from an accounting information system owned by each bank. The purpose of this research is to determine how much the independent variables can influence the successful implementation of the accounting information system in banking. There are three independent variables analyzed, namely personality characteristics, organizational structure and quality of business processes. The results of this study are expected to be useful for banks in implementing strategies when managing the quality of accounting information systems that will produce quality accounting information. The type of data used in this study is primary data obtained through distributing questionnaires to 46 banking companies in Indonesia. Verification analysis was performed using the SEM-PLS test tool. The results showed that problems in the quality of accounting information were caused by the application of accounting information systems that were not maximally integrated. Furthermore, it was found that the application of accounting information systems in banking organizations must be able to accommodate personality characteristics, organizational structure and quality of business processes.